2019
DOI: 10.1111/1471-0528.15870
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli‐containing vaginal probiotics to cure or prevent bacterial or fungal vaginal dysbiosis: a systematic review and recommendations for future trial designs

Abstract: Background Vaginal probiotics claiming to cure and/or prevent bacterial and/or fungal vaginal dysbiosis are available on the market but, until recently, did not have to be approved as drugs for human use. Objectives We evaluated the impact of vaginal probiotics on bacterial vaginosis (BV) and vulvovaginal candidiasis (VVC) cure and/or recurrence, as well as vaginal microbiota (VMB) composition and vaginal detection of probiotic strains. Search strategy We performed a systematic literature search in MEDLINE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…urogenital isolates have been well documented (Servin, 2004;Spurbeck and Arvidson, 2011;Petrova et al, 2013;Smith and Ravel, 2017). Clinical trials have confirmed the therapeutic interest of some of these strains to treat dysbiosis, BV and UTIs (MacPhee et al, 2010;Hanson et al, 2016;De Vrese et al, 2019;van de Wijgert and Verwijs, 2019). Here, we aimed to evaluate the distribution of a range of in vitro antimicrobial activities against BVassociated P. bivia and G. vaginalis, UPEC, and recurrent cystitis and infection-related preterm labor-associated E. coli in cervicovaginal strains of L. gasseri and L. crispatus.…”
Section: Introductionmentioning
confidence: 97%
“…urogenital isolates have been well documented (Servin, 2004;Spurbeck and Arvidson, 2011;Petrova et al, 2013;Smith and Ravel, 2017). Clinical trials have confirmed the therapeutic interest of some of these strains to treat dysbiosis, BV and UTIs (MacPhee et al, 2010;Hanson et al, 2016;De Vrese et al, 2019;van de Wijgert and Verwijs, 2019). Here, we aimed to evaluate the distribution of a range of in vitro antimicrobial activities against BVassociated P. bivia and G. vaginalis, UPEC, and recurrent cystitis and infection-related preterm labor-associated E. coli in cervicovaginal strains of L. gasseri and L. crispatus.…”
Section: Introductionmentioning
confidence: 97%
“…In their excellent systematic review, van de Wijgert and Verwijs suggest that lactobacilli‐containing vaginal probiotics hold promise for cure and prevention of bacterial vaginosis (BV), but not for vulvovaginal candidiasis. They call for more rigorous trials.…”
mentioning
confidence: 99%
“…We have since conducted a systematic review, which showed that long-term safety of vaginal probiotics has not yet been evaluated. 28 Our survey with women at recruitment sessions and enrolment visits showed that high-risk Rwandan women had heard of several STIs, but were generally unaware of BV, its causes and potential consequences, and what they can do to prevent it. Experiences with HIV show that public health interventions can only succeed if healthcare professionals and the public have sufficient knowledge of causes and consequences of disease.…”
Section: Discussionmentioning
confidence: 90%